Implementation of a Digital Leadership Model in Improving the Quality of Islamic Boarding Schools - Riski, Aulia; Chande, Abdin; Adriantoni (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to obtain information on how the implementation of the principal's digital leadership model has changed in improving school quality. The method used in this research is the descriptive method. This study took data using a qualitative approach with descriptive methods. The sampling technique uses the Purfocefull technique as a data collection technique. This research was conducted at Al Kamil Cianjur Modern Islamic Boarding School. The results of this study obtained information about how school principals implement digital leadership models in their schools. This research has implications that if this digital leadership model is applied in schools it can improve the quality of leadership which has implications for achieving previously planned goals.